Quantitative Analysis of Fatty Acids from Safflower by Selective and Sensitive Pre-Column Derivatization Method Using HPLC-FLD and Online APCI/MS - Zhang, Qiulong; Hu, Na; Li, Wencong; Bai, Bo; Wang, Honglun; Suo, Yourui; Ding, Chenxu; Wang, Xiaoyan (Asian Journal of Chemistry, 2015)
A pre-column derivatization method using 2-(11H-benzo[a]carbazol-11-yl) ethyl 4-methylbenzenesulfonate (BCETS) as labeling reagent followed by HPLC with fluorescence detection and on line APCI/MS for the determination and quantitative analysis of fatty acids from safflower has been successfully developed. The fatty acids could be easily and quickly labeled by BCETS at 95 ºC in the presence of K2CO3 as catalyst in DMF within 35 min. The derivatives exhibited excellent fluorescence property with excitation and emission wavelengths of 272 and 505 nm, respectively. The method displayed good selectivity, sensitivity, reproducibility and applicability. Qinghai and Xinjiang safflower (QHS and XJS), which were planted in different places in Qinghai province, were analyzed by the established method. The result showed the contents of total fatty acids, saturated fatty acids and unsaturated fatty acids from Qinghai safflower sample were all much higher than that from Xinjiang safflower sample, especially for Qinghai safflower sample planted in Datong county. The main unsaturated fatty acids were C18:1, C18:2 and C18:3 and the dominated saturated fatty acids were C16, C18 and C20, respectively. This work would be helpful for the safety assessment and quality control of the two kinds of safflowers.